Fluorescence in situ hybridisation for microbiological detection in mortars - R. Vieira (2015)
The aim of this work is to applied the FISH technique to the detection of the microorganisms of interest in materials of cultural heritage. FISH is a simple, rapid and promising technique enabling the detection, visualization and identification of the microorganisms. This technique is based on the hybridization of synthetic fluorochrome–labeled probes that bind to the target RNA [2,3,4]. The first steps to develop a protocol for microbiological detection in mortars have been taken. For satisfactory FISH results it is crucial to optimize the fixation and permeabilization of the cells. To determine the optimal fixation conditions, various fixation procedures – 4% paraformaldehyde and ethanol in different concentrations – were tested besides different fixation times for different eukaryotes. The detection of eukaryotes in synthetic mortars using a universal eukaryotic probe (EUK516) labeled with a fluorescent dye (Cy3) has been accomplished.